Impact of investment in research and development on growth and performance of dairy sector in Himachal Pradesh - Ratna, Jayant; Sharma, Krishan Dutt (Indian Journal of Dairy Science, 2017)
The present study examines the growth of dairy sector and quantifies the impact of R&D investments in dairy sector in Himachal Pradesh by using structural growth model, decomposition analysis and economic surplus approach using time series data. The study revealed that milk yield of cow and buffalo increased significantly in the state over the years. The results of decomposition analysis of growth showed that main increase in the milk production was due to yield effect rather than population effect. The regression analysis (Cobb Douglas production function) revealed that 1 per cent increase in number of crossbred cows and artificial insemination would increase the total milk production of the state by 0.64 and 0.90 per cent respectively. The overall economic surplus from milk production over the period 1993-94 to 2010-11 was estimated to be Rs. 222.04 crore from Rs. 157.64 crore of R&D investments with benefit-cost ratio of 1.41 and 62 per cent internal rate of return (IRR) The internal rate of return of R&D investment calculated by employing economic surplus model clearly indicated the remarkable impact of R&D investments in dairy development in Himachal Pradesh. The suggestions that came out of the study include the need to continue R&D efforts to improve the progeny of cows and buffaloes in order to increase the milk yield of bovine since their milk yields are still very less than the county’s average yield. Therefore, there is a need to continue R&D endeavours in dairy sector to harness the potential.